Estimation of Educational Requirements in Occupations and Occupational Groups - Weiermair, K. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1974)
This paper explores the usefulness of employer surveys for purposes of assessing and forecasting educational needs in occupations and occupational groups.